Less adolescent alcohol and cannabis use: More deviant user groups?. (18th August 2020) - Pape, Hilde; Rossow, Ingeborg
Abstract: Introduction and Aims: Adolescent drinking and cannabis use in Norway declined in the 2000s, and we tested the assumption that psychosocial problems were more strongly related to substance use when the prevalence was quite low (2012/2013) than when it was considerably higher (2002). Design and Methods: Data stemmed from school surveys of almost 20 000 students aged 14–17 years in 2002 and 2012/2013 in the four largest cities in Norway. We assessed how various deviant behaviours and depressive mood were related to past‐year measures on any alcohol intoxication, frequent intoxication (6+ times) and any cannabis use, and tested whether the associations varied significantly by survey year. Results: The prevalence of any intoxication episodes dropped markedly from 2002 (50%) to 2012/2013 (28%), as did the prevalence of frequent intoxication (29% vs. 10%) and any cannabis use (15% vs. 7%). Deviant behaviours and depressive mood were either more closely related to the drinking outcomes in 2012/2013 than in 2002, or the associations showed no temporal change. None of the associations with cannabis use varied significantly by survey year. Discussion and Conclusion: The assumption that psychosocial problems correlated more strongly with alcohol and cannabis use in a low‐prevalence period (2012/2013) as compared to a high‐prevalence period (2002) was partly supported, but only with respect to drinking. The strength of the associations with cannabis use was stable, which may reflect that the proportion reporting any use of the drug was low even in the relatively 'high‐prevalence' period.